Mucinous Colorectal Carcinoma Arising in Nonulcerated Villous Adenoma (MAVA): A Distinct Pathologic Entity - Naves, Ariel E.; Mortera, Monica (Revista Brasileira de Cancerologia, 2023)
Among 209 surgical specimens of resectable colorectal adenocarcinomas, nine mucinous carcinomas arising in nonulcerated villous adenoma (MA VA) were identified. They showed infUtration in the colorectal muscillaris própria or through it. However, their morphology was similar to the so-called pseudocarcinomatous submucous foci of villous adenomas. Only one of these tumors had lymph-node metastasis. We suggest that the mechanism of invasion of the colorectal wall in MAMA is diferent from that of the common adenocarcinoma, not implying an authentic carcinomatous transformation at cellular level.